Microplastic pollution on beaches in Crucita, Ecuador: Polymer abundance and composition - Bravo-Sánchez, Karen (2025)
Coastal environments worldwide face a significant and growing threat from microplastic pollution. This study quantified microplastic abundance and identified microplastic polymer types in the sand of three beaches in Crucita, Ecuador: Crucita (parish seat), Las Gilces, and La Boca. Sand samples were collected in September 2024 along 100-meter transects in the high tide zone. Ten sampling points were randomly selected per transect, and the subsamples were combined to form three composite samples per beach. The analytical process involved sorting the particles into two-dimensional categories: 1-5 mm (by sieving) and <1 mm (by density separation with NaCl and filtration). Microplastic abundance was quantified in both fractions. Polymer composition of the 1-5 mm fraction was analyzed using FTIR spectroscopy. For the 1-5 mm fraction, mean abundance was between 0.58 and 1.09 items/kg, whereas for the <1 mm fraction, it varied between 653.33 and 1,460 items/kg. Although abundance levels varied, the differences between the beaches were not statistically significant for either size fraction. Polypropylene was the most common polymer in the 1-5 mm fraction, followed by polyethylene and polyurethane. Notably, a terpolymer composed of styrene, acrylonitrile, and methyl methacrylate was identified exclusively at La Boca, the beach located at the mouth of the Portoviejo River. This finding strongly suggests a fluvial transport pathway for less common industrial polymers. These results provide the first baseline assessment of microplastic contamination in this area and highlight the need to implement waste management strategies for both land-based and riverine sources.